Super-resolution microscopy: Shedding new light on blood cell imaging - Huan Deng; Yan Ma; Yu-Hui Zhang (Journal of Innovative Optical Health Sciences)
Blood cells are the most integral part of the body, which are made up of erythrocytes, platelets and white blood cells. The examination of subcellular structures and proteins within blood cells at the nanoscale can provide valuable insights into the health status of an individual, accurate diagnosis, and efficient treatment strategies for diseases. Super-resolution microscopy (SRM) has recently emerged as a cutting-edge tool for the study of blood cells, providing numerous advantages over traditional methods for examining subcellular structures and proteins. In this paper, we focus on outlining the fundamental principles of various SRM techniques and their applications in both normal and diseased states of blood cells. Furthermore, future prospects of SRM techniques in the analysis of blood cells are also discussed.